Facile and Scalable Preparation of Ruthenium Oxide‐Based Flexible Micro‐Supercapacitors. Issue 6 (17th December 2019) - Brousse, Kévin; Pinaud, Sébastien; Nguyen, Son; Fazzini, Pier‐Francesco; Makarem, Raghda; Josse, Claudie; Thimont, Yohann; Chaudret, Bruno; Taberna, Pierre‐Louis; Respaud, Marc; Simon, Patrice
Abstract: Tremendous efforts have been invested in the development of the internet of things during the past 10 years. Implantable sensors still need embedded miniaturized energy harvesting devices, since commercialized thin films and microbatteries do not provide sufficient power densities and suffer from limited lifetime. Therefore, micro‐supercapacitors are good candidates to store energy and deliver power pulses while providing non‐constant voltage output with time. However, multistep expensive protocols involving mask aligners and sophisticated cleanrooms are used to prepare these devices. Here, a simple and versatile laser‐writing procedure to integrate flexible micro‐supercapacitors and microbatteries on current‐collector‐free polyimide foils is reported, starting from commercial powders. Ruthenium oxide (RuO2 )‐based micro‐supercapacitors are prepared by laser irradiation of a bilayered tetrachloroauric acid (HAuCl4 · 3H2 O)–cellulose acetate/RuO2 film deposited by spin‐coating, which leads to adherent Au/RuO2 electrodes with a unique pillar morphology. The as‐prepared microdevices deliver 27 mF cm −2 /540 F cm −3 in 1 m H2 SO4 and retain 80% of the initial capacitance after 10 000 cycles. This simple process is applied to make carbon‐based micro‐supercapacitors, as well as metal oxide based pseudocapacitors and battery electrodes, thus offering a straightforward solution to prepare low‐cost flexible microdevices at a large scale. Abstract : A versatile laser‐writing procedure to integrate flexible micro‐supercapacitors and microbatteries on current‐collector‐free polyimide foils is reported, starting from bilayered films containing tetrachloroauric acid (HAuCl4 · 3H2 O)–cellulose acetate and commercial powders of active material. This simple process allows carbon‐based and metal oxide based micro‐supercapacitors, and battery electrodes to be made, thus offering a straightforward solution to prepare low‐cost flexible microdevices at a large scale.